Optimizing Corporate Financial Performance through Good Corporate Governance and Leverage: A Literature Review - Maharani, Amalina; Putri, Yumna Syaza Kani; Khairany, Dea Giska (Dinasti Research & Yayasan Dharma Indonesia Tercinta (DINASTI), 2025)
This article aims to analyze the role of Good Corporate Governance (GCG) and leverage in enhancing corporate financial performance through a literature review approach. GCG, measured through ownership structure, board of directors, audit committee, and transparency, along with leverage policy, serves as a key factor in optimizing financial performance. This article reviews relevant literature linking these two variables to improvements in corporate financial performance and offers theoretical and practical implications that can serve as a foundation for further research. The literature review findings indicate that the implementation of effective GCG principles can enhance accountability, reduce information asymmetry, and promote better decision-making, thereby positively impacting profitability and firm value. Meanwhile, leverage has a complex influence; moderate debt use can increase return on investment through tax shields, but excessive leverage raises financial risk. The interaction between GCG and leverage also moderates their relationship with financial performance, where good governance can mitigate risks associated with leverage. The implications of this study highlight the importance of balancing GCG practices and leverage policies to achieve optimal financial performance. These findings are expected to serve as a reference for academics, practitioners, and regulators in making strategic decisions.